Discretionary Remote Working Helps Mothers Without Harming Non-mothers: Evidence from a Field Experiment - Sherman, Eliot L. (Management Science, 2020)
Because mothers remain disproportionately responsible for childcare, the daily requirement for physical presence at work disadvantages them compared with otherwise equivalent men and childless women. Relaxing this requirement may therefore enhance the well-being and productivity of working mothers. I tested this idea with a randomized field experiment, using a within-subjects analysis from a repeated crossover design. The 187 participants in the experiment, which ran for four weeks and yielded 748 person-week observations, revealed a preference for about two remote working days per week. I observed no significant differences in the uptake of remote working days between men, women, parents, nonparents, fathers, and mothers. Mothers reported meaningfully reduced family–work conflict during remote working weeks, but fathers did not. Remote working generally increased job performance, but the effect was greatest for mothers. The coordination costs of remote working, with respect to coworker helping and job interdependence, did not appear prohibitive. Interviews with study participants corroborate and contextualize these findings. This paper was accepted by Olav Sorenson, organizations.